2013
DOI: 10.1016/j.acap.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of the Effect of Centralized Reminder/Recall on Immunizations and Preventive Care Visits for Adolescents

Abstract: Objective-To assess the impact of a managed care-based patient reminder/recall system on immunization rates and preventive care visits among low-income adolescents.Methods-We conducted a randomized controlled trial between December 2009 and December 2010 that assigned adolescents aged 11-17 years to one of three groups: mailed letter, telephone reminders, or control. Publicly insured youths (n = 4, 115) were identified in 37 participating primary care practices. The main outcome measures were immunization rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 53 publications
(72 reference statements)
3
96
2
Order By: Relevance
“…They found improved vaccination rates among those who received reminders but no significant difference based on modality. 74 Chao et al demonstrated increased HPVV completion rates among participants randomized to receive reminder letters versus standard of care (56.4% vs 46.6%). 62 Both investigators identified a lack of reliable contact information as a barrier to implementation.…”
Section: Behavioral Interventions: Patienttargeted Reminder Interventmentioning
confidence: 99%
See 2 more Smart Citations
“…They found improved vaccination rates among those who received reminders but no significant difference based on modality. 74 Chao et al demonstrated increased HPVV completion rates among participants randomized to receive reminder letters versus standard of care (56.4% vs 46.6%). 62 Both investigators identified a lack of reliable contact information as a barrier to implementation.…”
Section: Behavioral Interventions: Patienttargeted Reminder Interventmentioning
confidence: 99%
“…62 Both investigators identified a lack of reliable contact information as a barrier to implementation. 62,74 Another trial randomized patients to receive telephone and mail reminders versus standard of care and showed significantly higher initiation (26.5% vs 15.3%) and completion rates (11.4% vs 4.4%) among the intervention group. 35 Two interventions used text message reminders; both showed significantly higher rates in the intervention group (51.6% vs 35%) 67 and (16% vs 5%).…”
Section: Behavioral Interventions: Patienttargeted Reminder Interventmentioning
confidence: 99%
See 1 more Smart Citation
“…To capitalize on this opportunity, future studies should seek to better understand which of the AFIX quality improvement strategies are most effective for increasing adolescent vaccine coverage, while continuing to explore approaches, such as webinar delivery, for maximizing program efficiency. In the long term, understanding how AFIX compares with other evidence-based strategies, such as centralized reminder/recall, [14][15][16] will also be important for helping state health departments allocate limited funds for immunization quality improvement.…”
Section: Discussionmentioning
confidence: 99%
“…For adolescents who were not caught up with vaccinations at the start of the study, uptake significantly increased by 21% for mail-reminder groups and by 17% for telephone-reminder groups versus only 13% for control groups. 48 A study on HPV vaccination rates, conducted in managed care organizations, found that text message reminders had a modest effect on HPV dose 1 rates for those who were able to receive the text message with valid phone numbers in the database. 49 In another study, postal mail, e-mail, or text reminders were used to improve adolescent vaccination rates.…”
Section: Reminder/recall Systems For Patientsmentioning
confidence: 99%